HASIL MENULIS KARANGAN SEDERHANA PESERTA DIDIK KELAS X IPA 2 SMAN 1 DRIYOREJO DENGAN METODE CHAIN WRITING - R. Calon, Dorotea (LATERNE, 2017)
This study examines the outcomes of learning the German language writing skills of students of class X IPA 2 SMAN 1 Driyorejo. This title has been selected on the basis problem in learning the German language which has a different structure of writing compared to other languages, such as the use of the article and change the verb that causes learning the German language into something that is not easy for learners, especially in writing skills are the skills most complex when compared with other language skills. Therefore Chain Writing method is used to facilitate students in learning the German language writing skills. The problem of this research is "How does learning outcomes writing skills of students of class X IPA 2 SMAN 1 Driyorejo with method Chain Writing". The purpose of this study was to describe the learning outcomes of students in grade X SMAN 1 IPA 2 Driyorejo in writing skills with Chain Writing method. The instrument of this study is a simple essay writing test and non-test observation sheet form. The research data obtained from the students learn writing skills during four meetings. The data obtained and analyzed by the assessment rubric writing skills and described with words such as excellent, good, fair, less, and others. The study of students showed an increase at every meeting. At the first meeting, without treatment methods, only 5 students who obtained the results of the predicate Very Good. At the beginning of the treatment methods at the confluence of two, there is one group that is predicated Very Good. In the treatment method at the confluence of three, there are two groups were predicated Very Good, and the treatment methods in four meetings, there are 4 groups predicated Very Good. At the end of the individual tests after learning method is applied, the study of students increased compared to the beginning of the meeting the test. At the end of the test, there are 16 learners predicated Very Good. From the learning outcome is obtained, it can be concluded that the method Chain Writing can facilitate learners in learning writing skills. Keywords : learning outcomes, writing essays, Chain Writing method